Evaluation of differential disaccharide excretion in urine for non-invasive investigation of altered intestinal disaccharidase activity caused by alpha-glucosidase inhibition, primary hypolactasia, and coeliac disease. Issue 3 (September 1996) - Bjarnason, I; Batt, R; Catt, S; Macpherson, A; Maxton, D; Menzies, I S
Abstract : BACKGROUND/AIM: The reliability of a quantitative method for the non-invasive assessment of intestinal disaccharide hydrolysis was assessed. METHODS: Differential excretion of intact disaccharide, expressed as ratios of lactulose to appropriate hydrolysable disaccharides in urine collected following combined ingestion, has been investigated in healthy volunteers with drug induced alpha-glucosidase inhibition, in subjects with primary hypolactasia, and patients with coeliac disease. RESULTS: Oral administration of the alpha-glucosidase inhibitor 'Acarbose' (BAY g 5421, 200 mg) together with sucrose and lactulose increased the urinary sucrose/lactulose excretion ratios (% dose/10 h) fivefold. The effect was quantitatively reproducible, a higher dose of 'Acarbose' (500 mg) increasing the excretion ratio to about 1.0 indicating complete inhibition of intestinal sucrase activity. The suitability of the method for measuring differences in dose/response and duration of action was assessed by comparing three different alpha-glucosidase inhibitors (BAY g 5421, BAY m 1099, and BAY o 1248) and found to be satisfactory. Subjects with primary adult hypolactasia had urine lactose/lactulose excretion ratios raised to values indicating reduced rather than complete absence of lactase activity whereas sucrose/lactulose ratios were not significantly affected. 'Whole' intestinal disaccharidase activity assessed by this method demonstrated impairment of lactase, sucrase, and isomaltase in eight, one, and seven, respectively, of 20 patients with coeliac disease. By contrast in vitro assay of jejunal biopsy tissue indicated pan-disaccharidase deficiency in all but five of these patients. This shows the importance of distinguishing between 'local' and 'whole' intestinal performance. CONCLUSIONS: Differential urinary excretion of ingested disaccharides provides a reliable, quantitative, and non-invasive technique for assessing profiles of intestinal disaccharidase activity.